2016
DOI: 10.1002/2016jd024860
|View full text |Cite
|
Sign up to set email alerts
|

Grey zone simulations of the morning convective boundary layer development

Abstract: Numerical simulations of two cases of morning boundary layer development are conducted to investigate the impact of grid resolution on mean profiles and turbulent kinetic energy (TKE) partitioning from the large eddy simulation (LES) to the mesoscale limit. Idealized LES, using the 3‐D Smagorinsky scheme, is shown to be capable of reproducing the boundary layer evolution when compared against measurements. However, increasing grid spacing results in the damping of resolved TKE and the production of superadiaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 35 publications
(106 reference statements)
2
31
0
Order By: Relevance
“…Wyngaard (2004) has pointed out that moderately fine resolution may have difficulty dealing with planetary boundary layer (PBL) parameterizations: conventional PBL schemes do not assume that cases exist in which some turbulence eddies are resolved while many other smaller scale eddies have to be parameterized. Such a resolution range is referred to as a "gray zone" or "Terra Incognita" for which a suitable parameterization is still under discussion for PBL convection (e.g., Honnert et al 2011;Zhou et al 2014;Ito et al 2015;Shin and Hong 2015;Efstathiou et al 2016;Kitamura 2016). Another study suggested a horizontal grid spacing of ~100 m is required to faithfully reproduce cumulus clouds (Bryan et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Wyngaard (2004) has pointed out that moderately fine resolution may have difficulty dealing with planetary boundary layer (PBL) parameterizations: conventional PBL schemes do not assume that cases exist in which some turbulence eddies are resolved while many other smaller scale eddies have to be parameterized. Such a resolution range is referred to as a "gray zone" or "Terra Incognita" for which a suitable parameterization is still under discussion for PBL convection (e.g., Honnert et al 2011;Zhou et al 2014;Ito et al 2015;Shin and Hong 2015;Efstathiou et al 2016;Kitamura 2016). Another study suggested a horizontal grid spacing of ~100 m is required to faithfully reproduce cumulus clouds (Bryan et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…There has also been similar work to investigate the behaviour of partially resolved turbulence in convective boundary layers -in particular the transition from high-resolution LES simulations to lower-resolution mesoscale simulations (Efstathiou and Beare, 2015). Efstathiou et al (2016) compared the representation of morning boundary-layer development in 50 m LES with two grey zone boundary-layer implementations at lower resolutions (down to 3,200 m). They evaluated the resulting deficiencies in either evolution of turbulent kinetic energy (TKE) or the amount of instability in the profiles and concluded that both formulations have strengths and weaknesses which highlights the inevitable issues with resolutions that are currently computationally feasible.…”
mentioning
confidence: 99%
“…The implementation of the PGB scheme as outlined here follows Efstathiou et al. () which may be consulted for full details. It is based on the approach of Boutle et al.…”
Section: Sub‐grid Schemesmentioning
confidence: 99%
“…Efstathiou et al. () tested a simple version of the PGB scheme in the Met Office large‐eddy model (LEM) and compared it with the bounding approach (Efstathiou and Beare, ) for idealized simulations of an evolving convective BL (CBL) in the grey zone. In the LEM framework, PGB was able to reproduce first‐ and second‐order quantities at both the LES and mesoscale limits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation